HLA‐A*11:256Q, a novel HLA‐A*11 variant, detected in a Taiwanese individual. (6th March 2017) - Yang, K. L.; Ng, J.; Lazaro, A.; Lin, P. Y.
Abstract : Nucleotide deletions from residues 409 to 417 of HLA‐A*11:02:01 results in a novel allele, HLA‐A*11:256Q .